Évolution des relations entre État et cinéma au Royaume-Uni (1979-2005) - Cecilia Tirtaine (Revue LISA)
A government can adopt two different stances regarding its domestic film industry. It may choose to support and protect it because of its cultural remit – or it may treat it like any other industry and adopt a laissez-faire attitude and let market forces determine its fate. The latter stance was adopted by the Thatcher government, which abolished the support system and protectionist measures from which British film had benefited for decades and granted it only few subsidies. The government severed almost all the existing links between the film industry and the State. These non-interventionist policies undoubtedly contributed to the dramatic drop in the number of British films produced and the chronic difficulties which the film industry experienced in the 1980s. The relationships between the government and the film industry have since changed considerably. The creation of the Film Council and the existence of a Film Minister within the government have definitely contributed to reinstating a dialogue between the industry and the government. State support in favour of film has increased dramatically in the past decade, with the introduction of tax incentives and new subsidies, which mostly derive from National Lottery revenues. The State’s investment in film is thus mainly indirect and it is clear that the government, by supporting British cinema, has in mind not only its contribution to the country’s culture but also to its economy. By changing the legal definition of a British film in order to entice into the UK foreign investors who want to benefit from attractive tax incentives, the government triggered an increase in the number of co-productions and foreign films shot in the UK – at the risk of undermining the identity of British cinema, and thus, the country’s culture.